Respostas
respondido por:
1
Olá!!!
Resolução!!!
f ( x ) = ax + b
• f ( 1 ) = 5 → a • ( 1 ) + b = 5 → a + b = 5
• f ( - 1 ) = - 1 → a • ( - 1 ) + b = - 1 → - a + b = - 1
Sistema :
{ a + b = 5
{ - a + b = - 1
——————— +
0 + 2b = 4
2b = 4
b = 4/2
b = 2
a + b = 5
a + ( 2 ) = 5
a + 2 = 5
a = 5 - 2
a = 3
a = 3, b = 2
f ( x ) = ax + b → f ( x ) = 3x + 2
Espero ter ajudado,!!
Resolução!!!
f ( x ) = ax + b
• f ( 1 ) = 5 → a • ( 1 ) + b = 5 → a + b = 5
• f ( - 1 ) = - 1 → a • ( - 1 ) + b = - 1 → - a + b = - 1
Sistema :
{ a + b = 5
{ - a + b = - 1
——————— +
0 + 2b = 4
2b = 4
b = 4/2
b = 2
a + b = 5
a + ( 2 ) = 5
a + 2 = 5
a = 5 - 2
a = 3
a = 3, b = 2
f ( x ) = ax + b → f ( x ) = 3x + 2
Espero ter ajudado,!!
Larissavazquez:
muito obrigadaaa
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás